Підвищення економічної ефективності роботи комунального підприємства - Опарій, Євгеній Олександрович; Корольова, Оксана Олександрівна (НТУ "ХПІ", 2018)
Фінансове становище підприємства допомагає визначити конкурентоспроможність і потенціал в діловому співробітництві, є гарантом ефективної реалізації економічних інтересів всіх учасників діяльності як самого підприємства, так і його партнерів. В результаті аналізу виявлені вразливі місця, що потребують особливої уваги. Нерідко виявляється достатнім виявити ці місця, щоб розробити заходи щодо їх ліквідації. Була запропонована інвестиційна програма щодо підвищення ефективності діяльності комунального підприємства "Теплопостачання та водо-каналізаційне господарство" м. Южноукраїнськ Миколаївської області.

Evaluations of the company's performance are carried out with the help of certain quantitative characteristics, which reflect the results of the enterprise and the company's expenses for the purposes of the activity, as well as some qualitative characteristics. The analysis of technical and economic indicators showed some deterioration of the results of the economic activity of the municipal enterprise "Heat supply and water and sewerage economy", which occurred mainly due to: the increase in the cost price of commodity products in connection with the increase in energy prices, losses in domestic networks, increase wage and salary costs, reduction of sales volumes in the tariff, unallocated volumes of heat and electricity, overheating in the heating of multi-apartment houses in the grid losses in excess of the lack of cover Shara insulation, and are not included in the tariff costs of thermal energy public places because of imperfect legislation. An investment program was proposed for improving the efficiency of the municipal enterprise "Heat supply and water-drainage economy" in uzhnoukrainsk, Mykolaiv region. From the point of view of the theory of time value of money, the main indicators of calculating the efficiency of investments are: net present value (NPV), internal rate of return (IRR), profitability index (PI) and payback period (PP). Analyzing the result, it is worth noting that the project can be considered pay-back and economically attractive.
Increasing the economic efficiency of the business of the municipal enterprise
Keywords: фінансово-господарська діяльність; інвестиції; коефіцієнт дисконтування; чиста теперішня вартість; річний чистий грошовий потік; ставка дисконтування; дисконтований грошовий потік; індекс прибутковості; період окупності інвестицій; внутрішня норма прибутковості; financial and economic activity; investments; discount rate; net present value; annual net cash flow; discount rate; discounted cash flow; profitability index; payback period; internal rate of return